The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1002/2014jb011692
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the generation of the 2013 Lushan Earthquake (Ms 7.0), China

Abstract: Global seismic waveform inversion can provide information on where the 2013 M s 7.0 Lushan earthquake occurred in Sichuan Province, China, and how its aftershock sequence expanded. To investigate the generation mechanism of the Lushan earthquake and its relation to the 2008 Wenchuan earthquake (M s 8.0), 50 temporary seismic stations were installed in the source area following the Lushan earthquake. Crustal stress data were also collected along the Longmen-Shan Fault zone (LMFZ) to reveal its influence on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
82
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(89 citation statements)
references
References 43 publications
7
82
0
Order By: Relevance
“…Li et al [20] and Liu et al [14,15] also suggested that the unruptured segment is most likely to produce a large earthquake (M~7) by interpreting results from 3D a numerical interseismic deformation simulation and co-seismic Coulomb stress calculation. On the other hand, both geologic trenches and seismic profiling suggest a low probability of a large earthquake along the gap in the near future [13,46], which is also supported by our fault-coupling model. Before the 2008 Mw 7.9 Wenchuan earthquake, the "seismic gap" segment along the southern LMSF was shallowly coupled (<5 km) (Figure 3a).…”
Section: Seismic Hazard Along the Southern Lmsfsupporting
confidence: 81%
See 1 more Smart Citation
“…Li et al [20] and Liu et al [14,15] also suggested that the unruptured segment is most likely to produce a large earthquake (M~7) by interpreting results from 3D a numerical interseismic deformation simulation and co-seismic Coulomb stress calculation. On the other hand, both geologic trenches and seismic profiling suggest a low probability of a large earthquake along the gap in the near future [13,46], which is also supported by our fault-coupling model. Before the 2008 Mw 7.9 Wenchuan earthquake, the "seismic gap" segment along the southern LMSF was shallowly coupled (<5 km) (Figure 3a).…”
Section: Seismic Hazard Along the Southern Lmsfsupporting
confidence: 81%
“…The kinematic rupture process of the 2008 Mw 7.9 Wenchuan earthquake shows a unilateral propagation to the northeast (e.g., [2,9,10,44]), which was reported to be caused by the effect of the crustal material strength (e.g., [45][46][47]). Zhu and Yuan [47] simulated the dynamic spontaneous rupture process of the 2008 Mw 7.9 Wenchuan earthquake using a two-dimensional finite element method and concluded that the crustal material strength difference between the hanging wall and the footwall of the LMSF is a key factor leading to the unilateral propagation.…”
Section: Unilateral Rupture Propagation Of the 2008 Mw 79 Wenchuan Ementioning
confidence: 99%
“…Following the 2008 Wenchuan earthquake, numerous geophysical and geological surveys have provided constraints on the crustal and lithospheric structures of the eastern TP (Bai et al, ; Feng et al, ; Guo et al, ; Lei, Li, et al, ; Z. Liu et al, ; Z. Wang et al, , ; X. Wang, Li, et al, ; Wei et al, ; Z. J. Zhang et al, ). Most studies show that the Moho depth changes from ~60 km beneath the eastern TP to ~40 km beneath the SCB (Lei et al, ; H. Y. Li et al, ; Q. Y. Liu, van der Hilst, et al, ; C. Y. Wang et al, ; Xu & Song, ; P. Z. Zhang, ; Y. Q. Zhang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…We develop a quantitative modeling method and workflow to map the details of the Moho structure and high‐velocity anomalies in the lithosphere. Then, data on the crustal Poisson's ratio (Z. Wang et al, ), topography, major faults, and large earthquakes (Ms ≥ 7.0) are integrated to analyze the crustal structure of the LMS area. The 3‐D lithospheric models of the eastern TP enable us to characterize the relationship between the topography and the Moho structure, as well as the seismic hazard along the eastern margin of the Tibetan Plateau.…”
Section: Introductionmentioning
confidence: 99%
“…Its boundary faults include the Kunlun fault in the north, ManiYushu-Xianshuihe fault in the south, and Longmen Shan in the east [3,4]. A series of strong earthquakes have occurred around the Bayan Har block in the Tibetan Plateau since 1997, including Mani earthquake (Mw7.5 on November, 8,1997 UTC) in Xinjiang province along the Mani fault [5], Kunlun Shan earthquake (Mw7.8 on November, 14, 2001 UTC) in Qinghai province along the Kunlun Shan fault [6][7][8], Yutian earthquakes (Mw7.1 on March, 20, 2008 UTC and Mw6.9 on February, 12, 2014 UTC) in Xinjiang province along the Altyn Tagh fault [9][10][11], Wenchuan earthquake (Mw7.9 on May, 12, 2008 UTC) in Sichuan province along Longmen Shan fault [12][13][14], Yushu earthquake (Mw6.9 on April, 13, 2010 UTC) in Qinghai province along Yushu-Xianshuihe fault [15,16], and Lushan earthquake (Mw6.6 on April 20, 2013 UTC) [17,18]. These earthquakes have composed the main seismic activity zone in the Tibetan Plateau in the past decades years [3].…”
Section: Introductionmentioning
confidence: 99%